2014
DOI: 10.4111/kju.2014.55.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Tamsulosin Versus Tamsulosin With Tadalafil in Combination With Prednisolone for the Medical Expulsive Therapy of Lower Ureteric Stones: A Randomized Trial

Abstract: PurposeTo compare the safety and efficacy of tamsulosin and tamsulosin with the phosphodiesterase-5 inhibitor tadalafil in combination with prednisolone as medical expulsive therapies for lower ureteric stones.Materials and MethodsBetween July 2011 and December 2012, 62 adult patients presenting with distal ureteric stones sized 5 to 10 mm were randomized equally to treatment with tamsulosin (group A) or tamsulosin with tadalafil (group B). Therapy was given for a maximum of 6 weeks. In addition, patients in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 30 publications
(27 reference statements)
4
33
2
1
Order By: Relevance
“…7 We decided to use tadalafil on the basis of reports by Gratzke et al who demonstrated the role of phosphodiesterase inhibitors in relaxation of ureteric muscles in the rank order of vardenafil>sildenafil>tadalafil. Because tadalafil is more selective than sildenafil for PDE5 than PDE6 receptors, which are present in the retina, visual problems are less likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 We decided to use tadalafil on the basis of reports by Gratzke et al who demonstrated the role of phosphodiesterase inhibitors in relaxation of ureteric muscles in the rank order of vardenafil>sildenafil>tadalafil. Because tadalafil is more selective than sildenafil for PDE5 than PDE6 receptors, which are present in the retina, visual problems are less likely.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Currently, alpha-1 adrenergic receptor antagonists represent the treatment of choice for lower urinary tract symptoms as shown in many randomised controlled clinical trials. 5,6,7 Alpha-1 adrenergic receptors are present in ureteric smooth muscles and antagonists inhibit basal tone, peristaltic frequency, and ureteral contractions even in the intramural tract.…”
Section: Introductionmentioning
confidence: 99%
“…Improved erectile function was seen in 12.9% of patients receiving tadalafil. 25 The use of PDE5 inhibitors and its potential value in MET remain in its infancy. Future studies are required to assess the utility of PDE5 inhibitors in MET.…”
Section: Met For Distal Ureteral Stonesmentioning
confidence: 99%
“…24 Kumar and colleagues examined the use of tadalafil in conjunction with tamsulosin and corticosteroid therapy. 25 The paper was based on the assumption that by combining drugs acting through different mechanisms, better ureteric relaxation and reduction in intramural pressure could be achieved. Patients were divided into 2 groups.…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 99%
“…'ları boyutu 5 ile 10 mm arası değişen distal üreter taşına sahip 62 hastaya tamsulosin (Grup A) ve tamsulosin + tadalafil (Grup B) vermişlerdir (18). Yazarlar, Grup A'da %74.2, Grup B'de ise %83.9'luk bir taş düşürme oranı bildirmişlerdir.…”
unclassified